FAMILY DISPUTE MEDIATION IN POLEWALI VILLAGE, PINRANG REGENCY: AN ANALYSIS OF THE VILLAGE HEAD'S ROLE FROM A LEGAL SYSTEM PERSPECTIVE BY LAWRENCE M. FRIEDMAN - Ridha Nurul Mutia; Fikri; Zainal Said; Rusdaya Basri; Aris (Familia: Jurnal Hukum Keluarga, 2026)
Family disputes are common in rural communities and are generally resolved through non-litigation mechanisms that emphasize deliberation and family values. This study examines the role of the Village Head in mediating family disputes in Polewali Village, Pinrang Regency, by employing Lawrence M. Friedman’s legal system theory as an analytical framework. A qualitative approach was adopted, with data collected through interviews, observations, and documentation involving village officials, community leaders, and individuals who had experienced family disputes. The findings show that the effectiveness of mediation is supported by three elements of the legal system: legal structure, legal substance, and legal culture. The legal structure is reflected in the Village Head’s authority and social position, which enable him to gain public trust as a mediator. Legal substance is manifested in the integration of formal legal norms, customary values, and the principles of Islamic family law that guide the mediation process. Meanwhile, legal culture is evident in the community’s strong commitment to deliberation and its preference for peaceful settlement of family disputes. The mediation practices in Polewali Village demonstrate that law operates not only through formal rules but also through social values that are continuously maintained and observed within the community